2007
DOI: 10.1074/jbc.m609350200
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Mixed Esters of Butyric and Retinoic Acid Drive Cardiac and Endothelial Fate in Term Placenta Human Mesenchymal Stem Cells and Enhance Cardiac Repair in Infarcted Rat Hearts

Abstract: We have developed a mixed ester of hyaluronan with butyric and retinoic acid (HBR) that acted as a novel cardiogenic/vasculogenic agent in human mesenchymal stem cells isolated from bone marrow, dental pulp, and fetal membranes of term placenta (FMhMSCs). HBR remarkably enhanced vascular endothelial growth factor (VEGF), KDR, and hepatocyte growth factor (HGF) gene expression and the secretion of the angiogenic, mitogenic, and antiapoptotic factors VEGF and HGF, priming stem cell differentiation into endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
137
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(148 citation statements)
references
References 43 publications
(50 reference statements)
6
137
0
3
Order By: Relevance
“…The cells result in considerable improvements to ventricular function, capillary density and scar tissue (Ventura et al 2007) and similar findings have been reported using native rat AMSCs (Fujimoto et al 2009). Stem cells derived from prenatal chorionic villi were also successfully engineered into a living autologous heart valve, which could have postnatal applications for repairing congenital cardiac malformations (Schmidt et al 2006).…”
Section: Musclesupporting
confidence: 67%
“…The cells result in considerable improvements to ventricular function, capillary density and scar tissue (Ventura et al 2007) and similar findings have been reported using native rat AMSCs (Fujimoto et al 2009). Stem cells derived from prenatal chorionic villi were also successfully engineered into a living autologous heart valve, which could have postnatal applications for repairing congenital cardiac malformations (Schmidt et al 2006).…”
Section: Musclesupporting
confidence: 67%
“…As for hAEC, support for the hypothesis that some hAMSC may still display pluripotency that is characteristic of the pre-gastrulation embryonic cells from which they are derived has come from several recent studies which show that these cells are able to differentiate toward ''classic'' mesodermal lineages (osteogenic, chondrogenic and adipogenic) In 't Anker et al 2004;Portmann-Lanz et al 2006;Soncini et al 2007;Wolbank et al 2007), as well as toward cell types of all three germ layersectoderm (neural) (Portmann-Lanz et al 2006;Sakuragawa et al 2004), mesoderm (skeletal muscles, cardiomyocytes and endothelial) Ilancheran et al 2007;Ventura et al 2007;Zhao et al 2005) and endoderm (Wei et al 2003).…”
Section: Human Amniotic Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…In attempting to enhance the cardiac differentiation of placental cells, Ventura and co-workers found that a mixed ester of hyaluronan and butyric and retinoic acids (HBR) promoted cardiogenic/vasculogenic differentiation of human amniochorionic (AC)-derived cells and enhanced the expression of cardiomyogenic genes (GATA4, NKX 2.5) and proteins (sarcomeric myosin heavy chain and alpha sarcomeric actin). Furthermore, cells treated with HBR were also seen to express both cardiac and endothelial markers such as von Willebrand factor (vWF), and enhance cardiac repair in infarcted rat hearts Ventura et al 2007), thereby providing valuable indication as to the conditions which may prove most useful in directing cardiac differentiation of hAMSC for clinical application.…”
Section: Human Amniotic Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…Growth factors, such as the hepatocyte growth factor (HGF) and vascular endothelial growth factor (VEGF) play pivotal roles in a variety of normal and pathological processes, including tissue repair (1,2), embryonic development (3), tumorigenesis and neurodegenerative disorders (4). In the nervous system they are important cytokines with modulatory actions.…”
Section: Introductionmentioning
confidence: 99%